2020
DOI: 10.1371/journal.pone.0243461
|View full text |Cite
|
Sign up to set email alerts
|

An integrative systematic review of creative arts interventions for older informal caregivers of people with neurological conditions

Abstract: Objective We aimed to assess and synthesise the current state of quantitative and qualitative research concerning creative arts interventions for older informal caregivers of people with neurological conditions. Methods A systematic search was employed to identify studies that examined creative arts interventions for older informal caregivers, which were synthesised in this integrative review. We searched the following databases: MEDLINE, PubMed, EBSCO, CINAHL, EMBASE, PsycINFO, Cochrane Library, Scopus, Web… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(51 citation statements)
references
References 43 publications
(228 reference statements)
1
49
0
1
Order By: Relevance
“…Despite the heterogeneity regarding the kind of creative activities that the participants engaged in, there was a considerable overlap regarding the impact of these activities. In line with the results from previous studies (see Irons et al, 2020; see also Cameron et al, 2013), we found that engaging in creative activities can have an impact on an experiential, cognitive and emotional, as well as on a behavioural and interactional level. All five levels of impact were mentioned in the majority of the interviews.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Despite the heterogeneity regarding the kind of creative activities that the participants engaged in, there was a considerable overlap regarding the impact of these activities. In line with the results from previous studies (see Irons et al, 2020; see also Cameron et al, 2013), we found that engaging in creative activities can have an impact on an experiential, cognitive and emotional, as well as on a behavioural and interactional level. All five levels of impact were mentioned in the majority of the interviews.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, our findings indicate that at least some family members of persons with dementia engage in creative coping processes outside group settings and without the support of trained professionals. This is particularly interesting as the group setting is one of the most frequently mentioned factors when it comes to explaining the effectiveness of arts-based interventions (for an overview, see, Irons et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent scoping review on creative arts, including visual arts, literary arts, comedy, music, and dance identified only 26 studies [ 26 ], providing further support that this field remains largely under researched. Nevertheless, there is strong evidence in support of using participatory and participating arts for both people with dementia [ 26 ] and their informal carers [ 27 ], irrespectively of the art form. Despite the emerging extensive body of literature over the last five years, there is a lack of consensus in defining quality of life for people with dementia, or what actually encompasses it.…”
Section: Discussionmentioning
confidence: 99%
“…Creative arts interventions have a broad range of psychosocial benefits for caregivers when incorporated into everyday live (Iron et al, 2020). When creative and innovative methods are used with care staff, family members and allies of people with dementia, they can also be transformative, interrupting routine ways of thinking and inspiring aspects of the caring imagination (Kontos et al, 2020; Kontos et al, 2010).…”
Section: Methods For Caring Imaginationmentioning
confidence: 99%